Analisis Perilaku Konsumen Dalam Keputusan Pembelian Pakaian - Yermitha, Anjelye; Husbah, Husbah; Hidayat, Syamsul (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze consumer behavior in purchasing decision-making, focusing on the factors influencing the process. The factors examined include perception, attitude, and social influence. A quantitative approach was employed, using a survey method involving 100 respondents. Data were analyzed using linear regression analysis to measure the impact of each variable on purchasing decisions. The results indicate that social influence significantly affect purchasing decisions, while perception and lifestyle have a moderate impact. The implications of this study highlight the importance for companies to understand consumer needs that align with consumer preferences and values. This research is expected to serve as a reference for business managers in designing effective and data-driven marketing strategies.